(untitled) (Cadernos de Sociomuseologia, 2016)
The goal of this paper is to prepare a phenomenological research, with a view to the spatiality of “historic house museums”. This character is revealed through the consideration that any object has a multitude of meanings that only if limited at the moment that it enters into this relationship. Our starting point is the duplication of the object "historic house museums”: as an object to the inhabitant of the house and its constructions of meaning; and as an object facing the look and visitor expectation of the house, one who scrutinizes the shifting and intangible border that separates and unites time, space and significances woven by home-resident-visitor relationship. It is known that it is impossible to reconstruct with absolute and unquestioned loyalty the "aura" of the house of former times. The absence of residents and the spatio-temporal displacement are some of the factors that prevent a direct look at the house per se. What differentiates the "historic house museums”of other museums and stimulates the visitor, a peculiar receptivity, namely the curiosity to know, although displaced from their space-time and move themselves, the secret spaces of a historical character. Unlike the elements revealed by the inhabitant of the house, which belong to the scope of the public and exposed, we have with the "historic house museums”, the opportunity to access the intimate universe of the inhabitant, recreating the data, re-coloring environments. In this regard, the house open to visitors is revealed as favorable platform to a aestheticize that makes objects expressions, as does the visitor active artist intimate space. Keywords: Phenomenology, intimate space, "historic house museum”, Aesthetics